UNISWAP - A CASE STUDY OF DECENTRALIZED EXCHANGES ON THE BLOCKCHAIN - Koroļkovs, Nikolajs; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2023)
The paper takes a close look at an emerging industry - decentralized finance on the blockchain. The goal of this paper is to compare centralized order book (CLOB)-based exchanges to automated market maker (AMM)-based decentralized exchanges (DEX) and analyze the challenges that AMM-based DEXes are facing today using Uniswap as an example.